A comparative analysis of offline and online trials in Indonesia's digital legal transformation - Rais, Amin; Hanifah, Mardalena (Privietlab, 2025)
The digital transformation of Indonesia’s justice system has introduced online trials (e-litigation) as a significant innovation, in response to the limitations of conventional (offline) court proceedings. This study aimed to conduct a normative legal comparison of offline and online trial mechanisms by evaluating their respective advantages and disadvantages across four key dimensions: effectiveness, efficiency, accessibility, and adherence to the principles of procedural law. Using a normative juridical approach, this study draws upon statutory regulations, judicial doctrines, and recent scholarly literature to provide a comprehensive analysis of both trial formats. The findings indicate that offline trials maintain superiority in upholding the principle of openness and facilitating the direct examination of witnesses and defendants, thereby ensuring the authenticity and integrity of courtroom interactions. However, offline models are often constrained by inefficiencies related to costs, scheduling delays, and logistical burdens. Conversely, online trials demonstrate substantial improvements in administrative efficiency, time management, and geographic accessibility, making them particularly valuable during emergencies such as the COVID-19 pandemic. Nonetheless, they pose critical challenges, including technological disruptions, diminished quality of verbal and nonverbal communication, and potential infringements on the principle of transparency. Moreover, the Indonesian Criminal Procedure Code and the Law on Judicial Power emphasize that public access to trials constitutes a core component of judicial legitimacy. Considering these findings, this study underscores the necessity of regulatory refinement and technological enhancement to ensure that online trials uphold the same standards of justice, fairness, and procedural integrity as their offline counterparts do.